2009
DOI: 10.1007/s00531-009-0468-7
|View full text |Cite
|
Sign up to set email alerts
|

Feedback between erosion and active deformation: geomorphic constraints from the frontal Jura fold-and-thrust belt (eastern France)

Abstract: A regional tectono-geomorphic analysis indicates a Pliocene to recent rock uplift of the outermost segment of the Jura fold-and-thrust belt, which spatially coincides with the intra-continental Rhine-Bresse Transfer Zone. Elevated remnants of the partly eroded Middle Pliocene Sundgau-Forêt de Chaux Gravels identified by heavy mineral analyses allow for a paleo-topographic reconstruction that yields minimum regional Latest Pliocene to recent rock uplift rates of 0.05 ± 0.02 mm/year. This uplift also affected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 53 publications
(109 reference statements)
1
36
0
Order By: Relevance
“…Because of this constraint, our model results should be considered maximum estimates. The Doubs profile is given a rock uplift rate of 0.05 mm/yr [Madritsch et al, 2009], except for the Bresse Graben where we assume a subsidence of 0.1 mm/yr. All other parameters are the same as Table 1.…”
Section: B Multiple Capture Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this constraint, our model results should be considered maximum estimates. The Doubs profile is given a rock uplift rate of 0.05 mm/yr [Madritsch et al, 2009], except for the Bresse Graben where we assume a subsidence of 0.1 mm/yr. All other parameters are the same as Table 1.…”
Section: B Multiple Capture Methodsmentioning
confidence: 99%
“…[61] The Jura was tectonically active between 10 and 4 Ma [Ziegler and Fraefel, 2009], with some evidence suggesting continued deformation today [Madritsch et al, 2009]. By assuming a steady rate of rock uplift, we have likely oversimplified the tectonic history of the region, both spatially and temporally.…”
Section: Flexure and Tectonicsmentioning
confidence: 99%
“…Accordingly, the major thin-skinned deformation phase of the Jura between ca. 10 and 4 Ma was followed by thin-and thick-skinned (Laubscher 1986;Mosar 1999;Ustaszewski and Schmid 2007;Madritsch et al 2010a) deformation at low strain rates until recent times (Giamboni et al 2004a(Giamboni et al , 2004bBraillard 2006;Carretier et al 2006;Madritsch et al 2010a). Mosar (1999) suggested that this northward shift of basement deformation occurred in order to restore a stable orogenic wedge geometry as stacking of the External Massifs shifted the wedge to a supercritical state.…”
Section: Evolutionmentioning
confidence: 99%
“…The Bresse Grabens and Upper Rhine Grabens are linked by the RhineBresse Transfer Zone (RBTZ), a system of transtensional faults that accommodated the Eocene to present crustal extension by left-lateral slip (Fig. 1b); (Geissert et al 1976;Petit et al 1996;Giamboni et al 2004a, b;Madritsch et al 2010aMadritsch et al , 2010b.…”
Section: The Central European Rifts: Upper Rhine and Bresse Grabensmentioning
confidence: 99%
See 1 more Smart Citation